Measuring efficiency of Islamic banks: Evidence from Indonesia - Mohamad Fany Alfarisi; Syukri Lukman (Faculty of Economics, Universitas Islam Indonesia, 2019)
The present study investigates the efficiency of Islamic banks in Indonesia particularly for the period of 2014-2015. To meet that objective, the data envelopment analysis (DEA) particularly input-oriented, variable return to scale (VRS) has been employed. Additionally, twelve full-fledge Islamic commercial banks are included as the sample of the study. Having analysed using the DEA model, we find the average technical efficiency score of Islamic banks in 2014 is 0.843. In this regard, the inefficiency of Islamic banks is attributed equally to pure technical efficiency and scale efficiency. Moreover, the average technical efficiency score of Islamic banks for the year of 2015 is 0.832 which is lower than the previous year. The inefficiency of Islamic banks in 2015 is mainly contributed by the scale inefficiency. Moreover, the results reveal a declining productivity of Islamic banks during the period of study.